2007
DOI: 10.1038/sj.npp.1301409
|View full text |Cite
|
Sign up to set email alerts
|

D2 Receptor Occupancy of Olanzapine Pamoate Depot Using Positron Emission Tomography: An Open-label Study in Patients with Schizophrenia

Abstract: A long-acting depot formulation of olanzapine that sustains plasma olanzapine concentrations for over a month after a single injection is currently under development. This multicenter, open-label study explored D 2 receptor occupancy of a fixed dose of olanzapine pamoate (OP) depot given every 4 weeks. Patients (nine male, five female) with schizophrenia or schizoaffective disorder previously stabilized on oral olanzapine were switched to OP depot 300 mg by intramuscular injection every 4 weeks for 6 months. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 18 publications
3
44
0
Order By: Relevance
“…This pooled analysis is based on 7 olanzapine LAI clinical trials that were conducted in patients between March 2001 and December 2010: a single-dose pharmacokinetic study ( N  = 134, Study F1D-EW-LOBS), a 2-month pharmacokinetic study ( N  = 9, Study F1D-EW-LOBO), a receptor occupancy study ( N  = 14, Study F1D-EW-HGJW) [14], an 8-week randomized, placebo-controlled acute efficacy study (olanzapine LAI N  = 304, Study F1D-MC-HGJZ) [11], a 24-week randomized, oral olanzapine-controlled maintenance study (olanzapine LAI N  = 743, Study F1D-MC-HGKA) [10], a 2-year randomized, oral olanzapine-controlled open-label efficacy study (olanzapine LAI N  = 264, Study F1D-MC-HGLQ), and a 6-year open-label extension study ( N  = 931, Study F1D-MC-HGKB) [12]. In addition there was 1 trial (Study F1D-EW-LOBE, a 6-month pharmacokinetic study) that was not included in this analysis due to the fact that the injection-related AEs for that study were collected through active solicitation (27.8% of patients [ N  = 302] reporting an injection site-related AE) and thus were not comparable with those of the other studies, which relied solely upon spontaneous reporting of AEs.…”
Section: Methodsmentioning
confidence: 99%
“…This pooled analysis is based on 7 olanzapine LAI clinical trials that were conducted in patients between March 2001 and December 2010: a single-dose pharmacokinetic study ( N  = 134, Study F1D-EW-LOBS), a 2-month pharmacokinetic study ( N  = 9, Study F1D-EW-LOBO), a receptor occupancy study ( N  = 14, Study F1D-EW-HGJW) [14], an 8-week randomized, placebo-controlled acute efficacy study (olanzapine LAI N  = 304, Study F1D-MC-HGJZ) [11], a 24-week randomized, oral olanzapine-controlled maintenance study (olanzapine LAI N  = 743, Study F1D-MC-HGKA) [10], a 2-year randomized, oral olanzapine-controlled open-label efficacy study (olanzapine LAI N  = 264, Study F1D-MC-HGLQ), and a 6-year open-label extension study ( N  = 931, Study F1D-MC-HGKB) [12]. In addition there was 1 trial (Study F1D-EW-LOBE, a 6-month pharmacokinetic study) that was not included in this analysis due to the fact that the injection-related AEs for that study were collected through active solicitation (27.8% of patients [ N  = 302] reporting an injection site-related AE) and thus were not comparable with those of the other studies, which relied solely upon spontaneous reporting of AEs.…”
Section: Methodsmentioning
confidence: 99%
“…Mamo et al6 reported results on a study examining D(2) receptor occupancy of olanzapine LAI during a multicenter, open-label study exploring D(2) receptor occupancy of a fixed dose of olanzapine LAI given every 4 weeks. Patients with schizophrenia or schizoaffective disorder previously stabilized on oral olanzapine were switched to olanzapine LAI 300 mg by intramuscular injection every 4 weeks for 6 months.…”
Section: Receptor Binding Datamentioning
confidence: 99%
“…2 For most antipsychotics, positron emission tomography (PET) studies have suggested the presence of a therapeutic window of striatal D 2 receptor occupancy (65%Y80%) in younger patients 3,4 with extrapyramidal side effects (EPSs) more likely at more than 80% D 2 receptor occupancy. 4,5 This observation has been used to successfully predict the therapeutic dose range of new drugs 6,7 and contributed to the current recommended antipsychotic dose range, which is much lower than the very high doses that had been used historically. 8 However, these data are derived from small clinical PET studies that used different imaging and analytic methods and included sample sizes less than 20, reducing the reliability of the data in predicting clinical outcome.…”
mentioning
confidence: 96%